RANCANG BANGUN HOSE AND DUST COLLECTOR BRACKET DENGAN 3D PRINTER MATERIAL PETG FILAMENT UNTUK CNC ROUTER - Suparno, Joko; Wijaya, Anugerah Bima; Halim, Dimas Ardiansyah; Ramadhan, Aly Rizki; Suminar, Ratih Ratna (Departemen Teknik Mesin Fakultas Teknik Unversitas Negeri Padang, 2024)
The challenge of a CNC Router is the dust and small particles produced during the cutting process such as wood, aluminum or acrylic materials. These small particles can disturb the health of operators. 3D printing is a technology where materials are arranged layer by layer to produce three-dimensional products. PETG filament is a type of polymer that has a density of 1.38 g/cm3 and has the advantage of being weather resistant, not being damaged or losing color when exposed to UV light. PETG filament uses a printing temperature of 230°C-265°C. This bracket is designed to hold hoses and dust collector. The Bracket design can be installed on a CNC router machine without interrupting the cutting process or reducing the quality of the final result. The method used is Autodesk Inventor Professional 2023 student edition software for 3D design and UltiMaker Cura for the slicing process. This research resulted in a bracket design and prototype using a 3D printer. The bracket exhibits sufficient structural capability to hold the cooling hose and dust collector. There is a dimensional difference between the design measurements and the workpiece that has been made of 0.27 mm in the CNC Router head diameter and 0.1 mm in the hose diameter. This is due to the work tolerances and parameters used on the 3D printer machine. By implementing the Hose and Dust Collector Bracket, it is hoped that small particles can be reduced so that a clean and dust-free work environment can improve operator health and comfort.